Knowledge Management in Hotel Business: A Case Study of Centara Grand at Central Plaza Ladprao Bangkok - Thanya Asawapisitkul ธัญญา อัศวพิสิฐกุล; Watit Intuluck วาทิต อินทุลักษณ์ (Dusit Thani College Journal, 2018)
This research paper aims 1) to study the level of knowledge management by the perception of Centara Grand hotel’s employees at Central Plaza Ladprao Bangkok 2) to study organizational factors including leadership organizational culture organizational climate affecting to knowledge management in Centara Grand hotel at Central Plaza Ladprao Bangkok 3) to study factors affecting to knowledge management in Centara Grand hotel at Central Plaza Ladprao Bangkok. This research was survey research which employed both primary and secondary data. The sample of this research paper was a total of 248 Centara Grand hotel’s employees at Central Plaza Ladprao Bangkok. According to Multiple Regression Analysis Enter Method, the result concluded that the levels of knowledge management of Centara Grand hotel at Central Plaza Ladprao in total were on the high level and all three of organizational factors including leadership organizational culture organizational climate were also on the high level. Moreover, organizational climate had the highest effect on knowledge management (t-value = 5.191) followed by leadership and organizational culture (t-value = 3.930 and 3.357) respectively. These three factors were able to predict 52.6 % of knowledge management. The result suggested that to increase the performance effectiveness, organization should embrace organizational culture by creating shared objective plan in each department, open an opportunity to present an opinion and make agreement in order to lead organization to meet shared goals.